Prevalence of Hepatitis C Virus Infection Among Blood Donors and Certain Risky Groups in Diyala Province - Noaman, Nadhim Ghazal (Diyala Journal of Medicine, 2019)
Background: Although the prevalence of hepatitis C virus infection among the general population is generally low; however, the risk of chronic hepatitis C virus infection is still high in certain groups of patients particularly multiple recipients of blood or blood products Objectives: The present study aimed to determine the hepatitis C virus infection rate among unpaid blood donors and certain risky population in Diyala province. Materials and methods: The present study was conducted in Diyala province for the period from1st. August/ 2009 to 30th./May 2010. A total of 248 subjects were included and categorized in 4 study groups namely; unpaid blood donors, healthcare workers, thalassemia, hemodialysis patients. Blood samples were collected; sera were separated and kept frozen till use. Detection of anti- hepatitis C virus antibody was carried out in the Public Health Laboratory in Baquba, using the third generation ELISA technique (Bioelisa hepatitis C virus). Repeatedly positive sera by ELISA were confirmed by immunoblot assay (Lia Tek hepatitis C virus III) in the Central Public Health Laboratory-Baghdad. Data were statistically analyzed. Results: the results showed that the higher hepatitis C virus infection rate was recorded among thalassemia patients (26.2%), followed by hemodialysis patients (21.7%) and Healthcare workers (3.3%), while the lowest infection rate was recorded among blood donors (1.1%). Neither age nor gender has significantly increased the hepatitis C virus infection in study groups. hepatitis C virus infection increased as the duration of hemodialysis prolonged. Conclusion: the hepatitis C virus infection rate, although it is acceptable among blood donors, but is still high among certain risky population in Diyala province.